Methodology of Developing Physical Qualities of Young Volleyball Players (Aged 12-13) Based on the Cluster Approach (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article provides brief information about the methodology of developing the physical qualities of young volleyball players (aged 12-13) based on the cluster approach.